2021
DOI: 10.1016/j.ijscr.2021.106488
|View full text |Cite
|
Sign up to set email alerts
|

Surgical management of duodenal web in an adult presenting with melaena; Case report and literature review

Abstract: Introduction Duodenal web is a rare pathology presenting infrequently in adults. Diagnosis is challenging and definitive management is commonly delayed. We present a case of a patient with a late diagnosis of duodenal web, who underwent laparotomy, intraoperative gastroscopy and surgical removal of the web performed by two general surgeons. Case presentation A 32-year-old woman with a previous diagnosis of irritable bowel syndrome presented with a three day history of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Delayed diagnosis of this abnormality in adults is common, which can cause long-term complications such as malnutrition and weight loss. 7 It is suggested that on radiographic and endoscopic evaluation of patients at any age, the duodenal web should also be considered in order to prevent the long-term suffering of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delayed diagnosis of this abnormality in adults is common, which can cause long-term complications such as malnutrition and weight loss. 7 It is suggested that on radiographic and endoscopic evaluation of patients at any age, the duodenal web should also be considered in order to prevent the long-term suffering of patients.…”
Section: Discussionmentioning
confidence: 99%
“… 5 , 6 In adults, it is usually diagnosed with a delay, due to non-specific symptoms and difficult visualization of the web on endoscopy, and this delayed diagnosis usually leads to significant complications for the patient. 7 Differentiating whether the duodenal web in adults is congenital or acquired (e.g. as a result of long-term non-steroidal anti-inflammatory drugs use, or secondary to pancreatitis, ulceration, obstruction or abdominal surgery) could be difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Typical management often includes diagnostic laparoscopy or open laparotomy with duodenoduodenostomy or duodenotomy with excision of the duodenal web. 10 , 11 Complications of these more invasive methods can include anastomotic leak and stenosis with open procedures, resulting in longer hospitalization, patient recovery time, and greater resource utilization. 12 Endoscopic management in our patient’s case avoided the morbidity and complication profile associated with surgical resection of duodenal webs.…”
Section: Discussionmentioning
confidence: 99%